Perceived Obstacles Faced by Diabetes Patients Attending University of Gondar Hospital, Northwest Ethiopia - Bhagavathula, Akshaya Srikanth; Gebreyohannes, Eyob Alemayehu; Abegaz, Tadesse Melaku; Abebe, Tamrat Befekadu (Frontiers in Public Health, 2018)
Background Diabetes mellitus (DM) is a non-communicable, chronic, and progressive disease that can lead to serious complications and even to premature death. A closer understanding of the DM patients’ specific obstacles will provide a greater clarity of the factors influencing their disease-related quality of life and coping with daily life. The study aimed to evaluate the obstacles of DM patients attending ambulatory clinic of the University of Gondar Hospital (UOGH), Northwest Ethiopia. Methods A cross-sectional study was conducted from February to April 2017 at ambulatory clinic of the UOGH. A validated short version of the diabetic obstacle questionnaire was used. The internal reliability of the questionnaire was checked using Cronbach’s alpha and was found to be 92.5%. To determine any association between each of the nine sections of the questionnaire and age, sex, residence, educational status, and DM type, a binary logistic regression was performed. Results The mean age of respondents was 38.69 ± 15.39 years. Compared with patients with type 1 DM, patients with type 2 DM reported poorer relationships with medical professionals (adjusted odds ratio (AOR): 2.191, p-value = 0.027) and less support from families and friends (AOR: 1.913, p-value = 0.049). Patients coming from rural areas (AOR: 2.947, p = 0.002) and having no formal education (AOR: 2.078, p = 0.029) also received less support from families and friends. Conclusion DM patients in UOGH reported several obstacles related to patients’ relationship with health professionals, lack of support from their friends, lack of knowledge about DM, and lack of motivation to exercise. Effective efforts should be initiated to improve healthier environment to educate, care and preventive services for people with DM.